2008
DOI: 10.1152/jn.90714.2008
|View full text |Cite
|
Sign up to set email alerts
|

Balance of Increases and Decreases in Firing Rate of the Spontaneous Activity of Basal Ganglia High-Frequency Discharge Neurons

Abstract: of increases and decreases in firing rate of the spontaneous activity of basal ganglia high-frequency discharge neurons. J Neurophysiol 100: 3086 -3104, 2008. First published October 8, 2008 doi:10.1152/jn.90714.2008. Most neurons in the external and internal segments of the globus pallidus and the substantia nigra pars reticulata (GPe, GPi, and SNr) are characterized by a high-frequency discharge (HFD) rate (50 -80 Hz) that, in most GPe neurons, is also interrupted by pauses. Almost all (ϳ90%) of the synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 88 publications
2
10
1
Order By: Relevance
“…Contrasting with the report of Tang et al (2007), firing rates of neurons in the GPe (mean rate, 52 Hz) in our study were significantly lower than in GPi but also lower compared to the mean rates of ~65 Hz that are typically found in the GPe of healthy monkeys (Wichmann et al, 2002; Starr et al, 2005; Elias et al, 2008; Erez et al, 2011). Instead, average GPe rates were in the same range as values reported for patients suffering from Parkinson's disease (Favre et al, 1999; Starr et al, 2005; Tang et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrasting with the report of Tang et al (2007), firing rates of neurons in the GPe (mean rate, 52 Hz) in our study were significantly lower than in GPi but also lower compared to the mean rates of ~65 Hz that are typically found in the GPe of healthy monkeys (Wichmann et al, 2002; Starr et al, 2005; Elias et al, 2008; Erez et al, 2011). Instead, average GPe rates were in the same range as values reported for patients suffering from Parkinson's disease (Favre et al, 1999; Starr et al, 2005; Tang et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in excellent agreement with the mean rate of 71 Hz that was reported by the only available study investigating pallidal discharges in a cohort of CD patients (Tang et al, 2007). Thus, internal pallidal discharge rates of CD patients are grosso modo similar to those being reported for healthy nonhuman primates (Filion and Tremblay, 1991; Wichmann et al, 2002; Starr et al, 2005; Elias et al, 2008; Erez et al, 2011) but considerably higher compared to the generally low GPi rates reported for patients with other types of dystonia, in particular generalized forms (Vitek et al, 1999; Sanghera et al, 2003; Merello et al, 2004; Starr et al, 2005; Zittel et al, 2009). …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A possible explanation for this may lie in the uncorrelated nature of abnormal GPe activity observed in this study. GPe activation was shown to be able to effectively influence the activity of GPi neurons (Kita 2007), but due to the diffused pattern of GPe-GPi connectivity a synchronized activation of the GPe (or a subgroup of its neurons) is needed to effectively influence the GPi (Kita 2007 animals there is little or no correlated activity between individual GPe-GPi neurons (Elias et al 2008;Raz et al 2000). GPe-GPi correlations have been shown to emerge in some pathological conditions in which the GPe neurons throughout the nucleus fire in a synchronized manner Raz et al 2000).…”
Section: B Amentioning
confidence: 99%
“…In particular, we aimed to solve the apparent contradiction between a) anatomical studies showing that the GPi is an important target of a gabaergic inhibition from GPe [3] that is further thought to be powerful, as the synaptic targets in GPi are close to the soma [4], and b) electrophysiological studies that record very similar activities in both nuclei, at rest [5], in directional arm reaching tasks [6] and during eye closures [7]. Furthermore, the BG are supposedly the substrates of a generic selection process among cortical inputs, but the classical explanation of this selection stemming from the segregation between a direct pathway (with the "direct" striatal neurons targeting straight the GPi) and an indirect pathway (with the "indirect" striatal neurons targeting the GPe) is not compatible with primate anatomical data showing a nearly total overlap in the efferences of the striatal neurons.…”
mentioning
confidence: 99%